2020
DOI: 10.3897/zookeys.1005.56964
|View full text |Cite
|
Sign up to set email alerts
|

Rattlesnake (Crotalus spp.) distribution and diversity in Zacatecas, Mexico

Abstract: Mexico is home to a large number of reptile species and has one of the greatest diversities of venomous snakes, among which the rattlesnakes pertaining to the Crotalus genus stand out. Out of more than 40 species in the country, nine are found in Zacatecas: C. aquilus, C. atrox, C. basiliscus, C. lepidus, C. molossus, C. polystictus, C. pricei, C. scutulatus and C. willardi. Although these reptiles are important, due to their relevance in terms of ecology, cultural use and public health, their conservation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
3
1
0
Order By: Relevance
“…These results are consistent with those obtained for other rattlesnake species where temperature and precipitation ranges are important environmental factors in their distribution (Sunny et al, 2019;Lara-Galván et al 2020). Although it has also been suggested that these factors go beyond influencing physiological aspects of the species such as reproductive activity, they also influence other aspects related to their survival such as densities of predators, prey and competitors, weed cover and relative humidity (Yañez-Arenas et al 2020).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These results are consistent with those obtained for other rattlesnake species where temperature and precipitation ranges are important environmental factors in their distribution (Sunny et al, 2019;Lara-Galván et al 2020). Although it has also been suggested that these factors go beyond influencing physiological aspects of the species such as reproductive activity, they also influence other aspects related to their survival such as densities of predators, prey and competitors, weed cover and relative humidity (Yañez-Arenas et al 2020).…”
Section: Resultssupporting
confidence: 89%
“…This observation aligns with Robert Meidinger's comment (in Uetz et al 2023), questioning the altitudinal range of 1,780 m asl as being too high for C. stejnegeri, as evident by the low habitat suitability around Yamiroba in the municipality of San Dimas, Durango (Figures 2 and 3). This is consistent with the altitudinal preferences of rattlesnake species (Lara-Galván et al 2020;Serna-Lagunes et al 2020), highly adapted to their elevation ranges to develop their physiological activities. On the other hand, Reyes-Velasco et al (2013) suggested that C. stejnegeri could also be found in Nayarit, Sonora, and Chihuahua, although Figure 3 shows a high suitability of the habitat for the species in the north of Nayarit and southwest of Sonora, the state of Chihuahua does not present a marked suitability environment for the species.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Just as snakebite risk and incidence change with season, weather and time of day depending on human and snake activity patterns, they also show long-term temporal trends based on changes in climate, weather anomalies ( Ediriweera et al, 2018 ) and human land use. Notably, this is not only of medical relevance, but also poses important challenges to conservation ( Lara-Galván et al, 2020 ). As with other human-wildlife conflicts, the general public usually perceives snakes as a threat, but is less aware that they themselves also pose a threat to wildlife ( Nyhus, 2016 ).…”
Section: A Changing World: the Effect Of Land Use Change And Climate Change On Human-snake Interactionsmentioning
confidence: 99%